Mahāpurusha Jagannātha Dāsaṅka Rāsa pañcādhyāẏī - Jagannātha Dāsa, 1487-1547 (Buks eṇḍa Buks, 1979)
Critical edition of five chapters of the Oriya trancreation of the Bhāgavatapurāṇa, on the divine love of Krishna.